2023
DOI: 10.1038/s41598-023-46918-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of brain injury, disease and tasks on cognitive fatigue

Glenn R. Wylie,
Helen M. Genova,
Bing Yao
et al.

Abstract: Because cognitive fatigue (CF) is common and debilitating following brain injury or disease we investigated the relationships among CF, behavioral performance, and cerebral activation within and across populations by combining the data from two cross-sectional studies. Individuals with multiple sclerosis (MS) were included to model CF resulting from neurological disease; individuals who had sustained a traumatic brain injury (TBI) were included to model CF resulting from neurological insult; both groups were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Among the barriers mentioned by participants, there were aspects related to the difficulty in completing PROMs and the need for more information on their role and importance for service provision and improvement. The difficulties affecting completion were mostly related to TBI symptoms, such as memory impairment and response fatigue, which are commonly reported by individuals with TBIs ( 87 89 ). This calls for the need to keep PROMs conceptually relevant but also accessible and easy to understand, particularly in consideration of the cognitive challenges that might create an additional burden to people with a TBI engaging with self-reported outcome measures ( 90 , 91 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the barriers mentioned by participants, there were aspects related to the difficulty in completing PROMs and the need for more information on their role and importance for service provision and improvement. The difficulties affecting completion were mostly related to TBI symptoms, such as memory impairment and response fatigue, which are commonly reported by individuals with TBIs ( 87 89 ). This calls for the need to keep PROMs conceptually relevant but also accessible and easy to understand, particularly in consideration of the cognitive challenges that might create an additional burden to people with a TBI engaging with self-reported outcome measures ( 90 , 91 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the context of health, cognitive fatigue can exert a negative impact on diverse medical conditions, including multiple sclerosis [23,26,36], Parkinson's disease [37], and traumatic brain injury [2], where it can exacerbate the challenges of coping with these illnesses. A study [38] by Wylie et al showed that individuals who have suffered a traumatic brain injury (TBI) experience similar levels of cognitive fatigue (CF) as those with multiple sclerosis (MS), but both groups reported higher levels of CF compared to healthy control individuals.…”
Section: Impacts On Daily Lifementioning
confidence: 99%